Multimedia - Nishi, Kazuki (IntechOpen, 2010)
Multimedia technology will play a dominant role during the 21st century and beyond, continuously changing the world. It has been embedded in every electronic system: PC, TV, audio, mobile phone, internet application, medical electronics, traffic control, building management, financial trading, plant monitoring and other various man-machine interfaces. It improves the user satisfaction and the operational safety. It can be said that no electronic systems will be possible without multimedia technology. The aim of the book is to present the state-of-the-art research, development, and implementations of multimedia systems, technologies, and applications. All chapters represent contributions from the top researchers in this field and will serve as a valuable tool for professionals in this interdisciplinary field.